METODE DEMONSTRASI DALAM PEMBELAJARAN PAI UNTUK MEMOTIVASI DAN MEMBERIKAN PEMBELAJARAN YANG BERMAKNA - Rosfiani, Okta; Maulana, Rijal; ‘Azzah Amirah, Liza; Fauzi, Muhammad Akmal; Sofiyah, Sofiyah (FKIP Universitas Al Washliyah Medan, 2025)
This qualitative study seeks to evaluate the implementation of the demonstration method in Islamic Religious Education (PAI) learning and analyse its impact on learning motivation and the creation of meaningful learning for students. The background of the study is motivated by the phenomenon of PAI learning, which is often textual and less involved with concrete experiences, thus potentially reducing students' interest and profound understanding. Data were collected through participant observation, in-depth interviews with teachers and students, and document analysis at SDN Pondok Ranji 03, South Tangerang City, Banten. This study involved several students and one PAI teacher as subjects. Data analysis used the Miles and Huberman thematic analysis technique. The research findings revealed that 1) the demonstration method significantly increased students' learning motivation through visualisation of worship practices (such as ablution, prayer, or Islamic history); 2) demonstrations create meaningful learning by connecting religious values with real-life contexts; and 3) supporting factors include teacher creativity, authentic media, and active student participation, while the main obstacles are time allocation and the readiness of facilities. The conclusion of the study confirms that the demonstration method has the potential as an innovative strategy in PAI to build emotional-intellectual engagement and internalisation of religious values. The implication is that educators need to design contextual and reflective demonstrations to optimise holistic Islamic religious education learning.